Using Learning Videos to Improve Student Learning Outcomes in Social Sciences Subjects in Class VII of Jambi City Labor Middle School - Afrila, Diliza (International Journal of Multidisciplinary Sciences and Arts, 2024)
Research objectives are the most important component in learning after the student component as a learning subject. In the educational context, the issue of goals is a question of the mission and vision of an educational institution itself. The research that the researcher carried out was in the form of Classroom Action Research (PTK). Implementation of this Classroom Action Research (PTK) utilizes Learning Videos, so that students are directly involved in learning activities. This shows an increase from the previous cycle, namely in cycle I the value of student learning outcomes in social studies subjects using learning videos was 63.25. The highest score obtained by students was 90 and the lowest score obtained was 35. 11 students met the KKM of 70, and 9 students did not meet the KKM. The percentage of students who reach the KKM is 55%. This means that cycle II has fulfilled the expected student learning outcome category of completeness, namely 100%. Based on the research results, it can be concluded that the achievement of student learning outcomes through learning videos in social studies subjects shows an increase in student learning outcomes.